Penerapan Failure Mode and Effect Analysis (FMEA) dalam Analisis K3 di Proyek Kontruksi PT. W - Andika, Rio; Sundari, Susanti; Pratiwi, Mirandhi; Nudin, Burhan (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This research studies the analysis of occupational safety and health on the PLTU unit 9-10 Java Suralaya construction project using the FMEA method at PT. W. In companies there are still risks that cause work accidents to occur frequently based on company data. The aim of this research is to identify and provide recommendations for the risk of work accidents for workers in the company. The methodology used in this research is FMEA. The results of this research are that there are 5 types of work accidents, namely material scratches, material impacts, slips, electric shocks and falls from heights, with the highest RPN being material scratches (24.28); and the lowest RPN value is Falling from a Height (18.24). There is 1 critical category (scratched by material) and 4 non-crisis categories (struck by material, slipped, electrocuted, fell from a height). Keywords: FMEA, Fishbone Diagram, Occupational Health, Occupational Safety, Risk Priority Number